2004
DOI: 10.1097/01.sla.0000124292.21605.99
|View full text |Cite
|
Sign up to set email alerts
|

Wound Infection After Elective Colorectal Resection

Abstract: The incidence of incisional SSI in patients undergoing elective colorectal resection in our cohort was substantially higher than generally reported in the literature, the NNIS or predicted by an institutional surgical infection complication registry. Although some of these differences may be attributable to patient population differences, we believe these discrepancies highlight the potential limitations of systematic outcomes measurement tools which are independent of the primary clinical care team. Accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
340
5
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(377 citation statements)
references
References 35 publications
20
340
5
4
Order By: Relevance
“…SSI is the most common complication after colectomy, and obesity or overweight is thought to increase this risk by 2.5-to 5-fold as compared with patients of normal weight [13][14][15][16]. This risk may be related to the decreased oxygen tension in relatively avascular adipose tissue, differences in wound healing, greater wound size, or technical difficulties [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…SSI is the most common complication after colectomy, and obesity or overweight is thought to increase this risk by 2.5-to 5-fold as compared with patients of normal weight [13][14][15][16]. This risk may be related to the decreased oxygen tension in relatively avascular adipose tissue, differences in wound healing, greater wound size, or technical difficulties [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…1 Reported rates vary according to surgical procedure, spanning <1% for clean procedures 2 to 30% for some colorectal procedures. [3][4][5][6] Standardized surveillance has long been recognized as a minimum and necessary requirement for effectual prevention strategies, [7][8][9] and diminishing SSI rates have been noted following the implementation of surveillance programs. 10 Surveillance data have recently been used to evaluate appropriateness of surgical antimicrobial prophylaxis in the United States.…”
mentioning
confidence: 99%
“…One possibility for this cost difference may be SSI, as the 6 care measures have previously been shown to be associated with SSI, [6][7] and SSI increases costs following colectomy. [1][2][3] However, further work is necessary to investigate the pathway between these perioperative care elements and the ultimate cost per patient.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Recent work has shown that 6 perioperative care measures are associated with SSI in colectomy patients:…”
Section: S Urgical Site Infections (Ssi)mentioning
confidence: 99%